1994
DOI: 10.1128/aac.38.12.2917
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities to 10 antimicrobial agents of 1,220 Campylobacter strains isolated from 1987 to 1993 from feces of pediatric patients

Abstract: We report the in vitro antibiotic susceptibility of 1,220 strains belonging to the thermotolerant Campylobacter species, isolated from the feces of pediatric patients with diarrhea in the period from 1987 to 1993. The strains were identified as 1,148 C.jejuni isolates and 72 C. coli isolates. The overall results show that the strains showed drug resistance as follows: 51.8% to ampicillin, 4.4% to clindamycin, 2.6% to chloramphenicol, 21.2% to tetracycline, and 1% to gentamicin. Twenty-one strains (1.7%) displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 27 publications
8
35
0
2
Order By: Relevance
“…Several studies have also shown an increase in the occurrence of macrolide resistance among Campylobacter causing infections in man [24,46,52]. The reason for the high frequency of macrolide resistance among C. coli from pigs has not been finally determined.…”
Section: Resistance Occurrence and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown an increase in the occurrence of macrolide resistance among Campylobacter causing infections in man [24,46,52]. The reason for the high frequency of macrolide resistance among C. coli from pigs has not been finally determined.…”
Section: Resistance Occurrence and Trendsmentioning
confidence: 99%
“…Intravenous aminoglycosides is the treatment of choice for serious Campylobacter bacteraemia and other systemic infections. However, increases in the occurrence of Campylobacter, causing infections in man, that are resistant to macrolides and fluoroquinolones, have been reported in several countries [13,16,24,45,46,52,55,57]. In these cases other antimicrobial agents may be used for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the number of Campylobacter isolates resistant to fluoroquinolone (FQ) in patients and animals has been reported [2,18,21,23,25,27,28]. Several epidemiological studies have indicated a relationship between the use of FQ in veterinary medicine and an increase in FQ-resistant Campylobacter [2,23,25].…”
mentioning
confidence: 99%
“…Campylobacter es intrínsecamente resistente a penicilina G y cefalosporinas de primera generación debido a la débil unión de estos antimicrobianos con las proteínas de unión a penicilina (PBPs) 31 . Además, se ha descrito la adquisición de β-lactamasas como una causa importante de resistencia a β-lactámicos en esta bacteria [31][32][33] . En un estudio realizado por Tajada y cols, se determinó que de 100 cepas de C. jejuni y Campylobacter coli, 88% presentaban β-lactamasas y que, pese a la existencia de éstas, 77% de las cepas que las poseían eran susceptibles a amoxicilina 34 .…”
Section: Discussionunclassified